eCM 2015
DOI: 10.22203/ecm.v029a12
|View full text |Cite
|
Sign up to set email alerts
|

Local origins impart conserved bone type-related differences in human osteoblast behaviour

Abstract: Osteogenic behaviour of osteoblasts from trabecular, cortical and subchondral bone were examined to determine any bone type-selective differences in samples from both osteoarthritic (OA) and osteoporotic (OP) patients. Cell growth, differentiation; alkaline phosphatase (TNAP) mRNA and activity, Runt-related transcription factor-2 (RUNX2), SP7-transcription factor (SP7), bone sialoprotein-II (BSP-II), osteocalcin/bone gammacarboxyglutamate (BGLAP), osteoprotegerin (OPG, TNFRSF11B), receptor activator of nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 101 publications
0
19
1
Order By: Relevance
“…Although bone exhibits some highly conserved factors in its development, remodelling and repair, it is also apparent that the response to many in vivo challenges is not always consistent in different regions of bone [1][2][3]. These observations suggest that osteoblast populations are inherently heterogeneous and support a current hypothesis that their identity is specific to their local environment [4]. In recent attempts to clinically improve the success of joint replacement much focus has been on the study of the bone cell-implant interface with the long term success of joint replacement relying on sufficient osteoblast adherence, proliferation and differentiation in promoting osseointegration in specific regions.…”
Section: Introductionmentioning
confidence: 72%
“…Although bone exhibits some highly conserved factors in its development, remodelling and repair, it is also apparent that the response to many in vivo challenges is not always consistent in different regions of bone [1][2][3]. These observations suggest that osteoblast populations are inherently heterogeneous and support a current hypothesis that their identity is specific to their local environment [4]. In recent attempts to clinically improve the success of joint replacement much focus has been on the study of the bone cell-implant interface with the long term success of joint replacement relying on sufficient osteoblast adherence, proliferation and differentiation in promoting osseointegration in specific regions.…”
Section: Introductionmentioning
confidence: 72%
“…Power analysis indicated that a sample size of 8 humeri was required to achieve 80% power for each of the RM-ANOVA statistical analyses. For this power analysis, we chose our clinically meaningful difference in bone density to be 15%, which falls between the 10% and 20% values previously reported in the literature, 9 , 15 and our group standard deviations were ±0.037 g∙cm −3 as taken from pilot specimens.…”
Section: Methodsmentioning
confidence: 94%
“…This may be especially advantageous for patients who experience a marked decrease in bone density in the region of the greater tuberosity because of age while their bone density remains unchanged in the medial and posterior regions independent of age and sex as described by Barvencik et al. 1 In addition, Shah et al, 15 using osteoblasts derived from age-matched and paired humeral head samples with osteoarthritis and osteoporosis, showed that cortical and subchondral bone had greater proangiogenic (higher levels of vascular endothelial growth factor A messenger RNA and protein release) capacity and fracture healing characteristics compared with trabecular bone. Their trabecular bone sample taken from the central regions distal to the anatomic neck also consistently showed slower osteoblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Total cellular RNA was isolated from the homogenates using the PureLink RNA Mini Kit (Life Technologies) according to the manufacturer's protocol. RNA purity was validated using UV-vis spectroscopy absorbance; acceptable samples were characterized by 260/ 280 ratios N2.0 and 260/230 N 1.8 (Shah et al, 2015). Purified RNA was stored at −80°C prior to complementary DNA (cDNA) synthesis.…”
Section: Rna Isolationmentioning
confidence: 99%